Powers of freedom : reframing political thought - Rose, Nikolas S. (Cambridge University Press, 1999)
An impressive approach to an important and influential school of thought, derived from Foucault's writings on governmentality, by one of its major exponents. Nikolas Rose's book will serve as an intelligent and critical introduction to governmentality for students and scholars alike.
"Portions of this book draw on published and unpublished papers"--Acknowledgements
Keywords: Foucault, Michel -- Contributions in political science.; Foucault, Michel, -- 1926-1984; Foucault, Michel, -- (1926-1984) -- Contribution à la science politique.; Political sociology.; Liberty.; Communities.; Community life.; Sociologie politique.; Liberté.; Communauté.; freedom.; PHILOSOPHY -- Political.; Community life; Communities; Liberty; Political science; Political sociology; Politische Soziologie; Politieke macht.; Vrijheid.; Liberalisme.; Electronic books.